2017
DOI: 10.1097/gox.0000000000001596
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Autologous Platelet-Rich Plasma and Fat Graft Preparation Methods

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 77 publications
(148 reference statements)
0
19
0
1
Order By: Relevance
“…Certainly, many researchers also reported a similar positive effect of platelet-rich plasma (PRP) addition as an alternative approach in fat grafting. 31 However, for some patients with fat accumulation, extracting SVF from a large number of excess aspirated fat is better than extracting PRP from blood.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, many researchers also reported a similar positive effect of platelet-rich plasma (PRP) addition as an alternative approach in fat grafting. 31 However, for some patients with fat accumulation, extracting SVF from a large number of excess aspirated fat is better than extracting PRP from blood.…”
Section: Discussionmentioning
confidence: 99%
“…Due to early ischemia and hypoxia, adipose tissue with a diameter larger than 1200 um tend to necrosis at the central region after transplantation into the body 8 . Studies showed that implanted fat tissue can be classified into three zones from the periphery to the center at 4 weeks after transplantation: survival, regenerated, and necrotic zones 9 .…”
mentioning
confidence: 99%
“…2, 3, 4 [17]. Luck et al befassten sich in ihrem Review besonders mit den unterschiedlichen angewandten Techniken und konkludierten letztlich, dass die methodische Heterogenität und die zu unpräzise Beschreibung der Techniken in den einzelnen Publikationen eine aussagekräftige Bewertung erschweren [9]. Somit bleibt die Frage nach dem optimalen Protokoll nach wie vor offen und zeigt die Notwendigkeit methodisch korrekter, präzise dokumentierter klinischer Studien.…”
Section: Fallbeispieleunclassified